2019
DOI: 10.1109/jbhi.2018.2856535
|View full text |Cite
|
Sign up to set email alerts
|

Drug Repositioning for Schizophrenia and Depression/Anxiety Disorders: A Machine Learning Approach Leveraging Expression Data

Abstract: Development of new medications is a lengthy and costly process, and drug repositioning might help to shorten the development cycle. We present a machine learning (ML) workflow to drug discovery or repositioning by predicting indication for a particular disease based on drug expression profiles, with a focus on applications in psychiatry. Drugs that are not originally indicated for the disease but with high predicted probabilities serve as candidates for repurposing. This approach is widely applicable to any ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
40
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 89 publications
2
40
0
1
Order By: Relevance
“…Our secondary aim was to examine the utility of machine‐learning techniques to differentiate patients from HV using retinal vessel trajectory as the input variable. Several studies have used the machine‐learning approach to classify SCZ/BD and HV using neuroimaging/electrophysiologic/cognitive data as input variables . A recent study reported prediction accuracy of 76% to differentiate SCZ from HV using a multisite machine‐learning analysis .…”
Section: Discussionmentioning
confidence: 99%
“…Our secondary aim was to examine the utility of machine‐learning techniques to differentiate patients from HV using retinal vessel trajectory as the input variable. Several studies have used the machine‐learning approach to classify SCZ/BD and HV using neuroimaging/electrophysiologic/cognitive data as input variables . A recent study reported prediction accuracy of 76% to differentiate SCZ from HV using a multisite machine‐learning analysis .…”
Section: Discussionmentioning
confidence: 99%
“…ML approaches such as deep learning and other methods hold great promise for accelerating drug discovery/repositioning, as they may be able to discover and predict with higher accuracy the complex patterns and relationships between genes, drugs and diseases [130] , [131] , [132] , [133] . For example, ML methods may be used to capture complex relationships between drug transcriptome and the drug’s treatment potential for specific diseases [134] . For diseases with high heterogeneity, a drug may only be useful for a subgroup of patients [135] .…”
Section: Discussionmentioning
confidence: 99%
“…Huge data generated by High-throughput Next Gen Sequencing (NGS) from numerous patients when combined with disease characteristics and treatment options can lead to the identification of new disease biomarkers and drug targets(Stupnikov et al 2018;Zai et al 2018). AI-driven supervised machine learning algorithms can implement multiomics and multitask learning to facilitate drug response elicited by engagement of multiple drug targets(Nascimento et al 2019;Nath et al 2018;Saberian et al 2019;Zhao and So 2019).…”
mentioning
confidence: 99%